Peut-on lire Only Revolutions de Mark Z. Danielewski ? - Alexandre Palhière (Sillages Critiques)
This article focuses on the first two pages of Mark Z. Danielewski’s novel, Only Revolutions, published in 2006. These two pages are the incipits of the two protagonists’ stories, Sam and Hailey, and give a first insight into the problems this book raises. The main concern of this analysis is therefore the difficulty for any reader who is used to a linear reading process to apprehend such a text. How can one read such a novel? Where should one begin? What kind of link can one establish between the different texts within the book? While shedding light on the relations between myth, history and story within the crucible of poetry, Mark Danielewski also seems to renew this questioning thanks to his use of technological progress, the multiple possibilities it has given allowing him to redefine the link between the writing and reading processes.